2021
DOI: 10.1073/pnas.2102233118
|View full text |Cite
|
Sign up to set email alerts
|

A neural surveyor to map touch on the body

Abstract: Perhaps the most recognizable sensory map in all of neuroscience is the somatosensory homunculus. Although it seems straightforward, this simple representation belies the complex link between an activation in a somatotopic map and the associated touch location on the body. Any isolated activation is spatially ambiguous without a neural decoder that can read its position within the entire map, but how this is computed by neural networks is unknown. We propose that the somatosensory system implements multilatera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

6
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 83 publications
(141 reference statements)
0
4
0
Order By: Relevance
“…Instead, the present results are more in line with a functional account of embodiment, where sensorimotor computations are merely re-used during tool use. Localizing touch on a rods may involve similar sensorimotor transformations (Yamamoto & Kitazawa, 2001), somatosensory computations (Miller et al, 2022;Miller et al, 2021), and neural processes (Miller et al, 2019) as localizing touch on the body. Given the high localization accuracy observed in the present study, we propose that this is also the case when localizing touch on rods of extreme length.…”
Section: Methodsmentioning
confidence: 99%
“…Instead, the present results are more in line with a functional account of embodiment, where sensorimotor computations are merely re-used during tool use. Localizing touch on a rods may involve similar sensorimotor transformations (Yamamoto & Kitazawa, 2001), somatosensory computations (Miller et al, 2022;Miller et al, 2021), and neural processes (Miller et al, 2019) as localizing touch on the body. Given the high localization accuracy observed in the present study, we propose that this is also the case when localizing touch on rods of extreme length.…”
Section: Methodsmentioning
confidence: 99%
“…The brain does not represent the angles, lengths, and locations as individual point estimates but rather as probability distributions. 15 This is because the activity within the nervous system is intrinsically noisy, from transduction of signals to network interactions. 16 To deal with this uncertainty, the brain must rely on probabilistic processing, as formalized by Bayesian decision theory.…”
Section: A Bayesian Model Of Finger Perceptionmentioning
confidence: 99%
“…Because it is essential to identify the position of a tactile object in order to interact with it, more than a century of research has characterized the perceptual processes underlying tactile localization at a behavioral level (Miller et al, 2022;Liu & Medina, 2021;Fuchs, Wulff, & Heed, 2020;Sadibolova, Tamè, & Longo, 2018;Badde, Röder, & Heed, 2015;Mancini, Longo, Iannetti, & Haggard, 2011;Harrar & Harris, 2009;Ho & Spence, 2007;Cholewiak & Collins, 2003;Stevens, 1992;Parrish, 1897;Weber, 1846; for a review, see the work of . These studies have identified different spatial codes that are utilized to localize tactile stimuli.…”
Section: Introductionmentioning
confidence: 99%